The Gifts of the Spirit in 1 Corinthians 12:1-11 and their Usage in Some Selected Pentecostal and Charismatic Churches in Kumasi - Yankyera, Patrick (Rev.) (2015)
A Thesis Submitted to the School Of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in Partial Fulfillment of the Requirements for Award of Master of Philosophy in Religious Studies